Soy and Dragon Fruit Functional Drink : The Potential to Reduce Cholesterol Total Levels in Hypercholesterolemic Sprague Dawley Rats - Suryana, Arinda Lironika; Putri, Chindy Yulita Krismuntiani; Rosiana, Nita Maria; Arum, Puspito (Indonesian Journal Publisher, 2024)
Hypercholesterolemia is a lipid metabolism disorder characterized by increased blood cholesterol levels. The alternative functional drinks that can reduce cholesterol levels are beverage ingredients that contain flavonoids, such as red dragon fruit and soybeans. Flavonoids can inhibit cholesterol synthesis by inhibiting the HMG-CoA reductase enzyme. Soybeans are also have a hypocholesterolemic effect because they contain isoflavones. This study aimed to determined the potential of soybean and dragon fruit peel powder on the cholesterol levels of hypercholesterolemic Sprague Dawley rats. This study was a true-experimental design with a pretest - posttest with control group. The samples were 27 male Sprague Dawley rats, weighing 150-250 grams and aged 2 -3 months. The samples were divided into a control group and a treatment group that was given soybeans dragon fruit peel powder drink at a dose of 12.8 ml/kgBB/day for 14 days. Total cholesterol levels were measured using the CHOD–PAP method. Data were analyzed using the One Way Anova test, Post Hoc or Man Whitney test and Paired T-test. The results showed that there was a significant difference in total cholesterol levels in mice before and after the intervention (p= 0.003). Giving soybeans dragon fruit peels powder drink can significantly reduce total cholesterol levels in the treatment group (P) by 18.45% (p= 0.044).